A Hückel method application for studying the self-assembly of phthalocyanine monolayers - Fields, Connor J.B. (2020)
The modern day applications of quantum chemistry offer a vast scope of choices and tools available to researchers working in that field. These ideas range from techniques working close to the quantum fundamentals, i.e. performing wavefunction calculations, to those taking purely classical perspective in which molecular properties might be deduced from observing the potential of the system [1, 2, 3, 4]. A relatively old and often overlooked idea for this type of work is the so-called H\"uckel method. This thesis will argue that under the right conditions this concept is a legitimate and powerful tool that has the potential for studying the behaviour of molecular systems. The idea for this research derives from a paper published by J. Leaf et al in 2016 [5], where the H\"uckel method was used to calculate and investigate the electronic properties of buckminsterfullerene molecules ($C_{60}$). This work follows on from that research by performing similar H\"uckel based calculations on a variety of different phthalocyanine molecules. A significant part of the work described in this thesis is devoted to examining how a H\"uckel method simulation can be applied to aid the interpretation of scanning tunnelling microscope (STM) images. Recognizing this, detailed images will be presented as part of the discussion of the molecular assembly to clarify detail, provide a visualisation of the effects being presented and give insight into the STM images viewed in experiments. Despite the relative simplicity, and, importantly, very low computational cost of the H\"uckel method (particularly when compared to, density functional theory calculations, for example), the program shows that it can produce simulated data that not only replicate the real-world STM results but predict novel molecular monolayer structures. In this thesis, two key types of molecule, and molecular assembly, are investigated using the H\"uckel method: benzene (as a prototyping tool) and a collection of phthalocyanine molecules. The adsorption of the latter on a variety of surfaces is explored, using experimental data as a check on the program where it is available. Using these tools, accurate simulations of titanyl phthalocyanine (TiOPc) on a gold surface were obtained, according to the results published by Mannsfeld and Fritz in 2005 [6]. An investigation of the effect of changing the molecular super-lattice structure was also performed showing a small linear change between the minimum molecular angle and inter-molecular distance. The simulations further predicted six angular phases in a comprehensive assessment of each phthalocyanine on three different surfaces, in three different overlayer structures. Included in this discussion is a qualitative comparison with STM images published by Bobaru and Salomon et al in 2011 [7]. These again show excellent agreement with simulations performed in this research. Hence demonstrating the validity of these simulation techniques.